Presence of paroxysmal nocturnal hemoglobinuria in patients with idiopathic portal vein thrombosis: a single-center study - Demir, Cengiz; Ebinc, Senar; Ekinci, Omer (Tubitak Scientific & Technological Research Council Turkey, 2020)
Background/aim: Paroxysmal nocturnal hemoglobinuria (PNH) is a very rare clonal hematopoietic stem cell disease characterized by chronic hemolytic anemia and thrombosis. We report data from a study of the occurrence of PNH among patients with idiopathic portal vein thrombosis (PVT). Materials and methods: Patients who were followed up with the diagnosis of idiopathic PVT were enrolled into this study. Those with laboratory and/or imaging evidence of any local or systemic factor that could lead to PVT were excluded. PNH clone was examined in all patients using established FLAER methodology. Results: A total of 112 patients (42 males and 70 females), none of them had a markedly PNH clone, but 4 patients (3.6%) with confirmed tests two times had small PNH clones (size between 3.02% and 4.62%). The median ages of PNH clone (-) and PNH clone (+) patients were 42 (range; 24-59) vs 39 (range; 36-42) years, respectively. The median hemoglobin concentration, platelet count and leukocyte count were lower in the PNH clone (+) group than the PNH clone (-) group. Anemia, thrombocytopenia, and leukopenia were detected in all PNH clone (+) patients. In addition, the PNH clone positivity size in monocytes was higher than erythrocytes in all of 4 patients. Conclusions: PNH should be considered during differential diagnosis among patients with idiopathic PVT. Small PNH clones can be detected in PVT patients that we cannot clearly determine its relationship with PVT. We need furthermore studies to explore the potential role of this finding.
Keywords: Portal vein thrombosis; paroxysmal nocturnal hemoglobinuria; FLAER